Ministry of Insurance and Social Affairs (Insurance Sector) Decree No. 54 of the Year 2013 Amending Schedule No. (1) "Occupational Diseases" Attached to the Social Insurance Law Promulgated by Law No. 79 of the Year 1975 = وزارة التأمينات والشئون الاجتماعية (قطاع التأمينات) قرار رقم 54 لسنة 2013 بتعديل الجدول رقم (1) - جدول أمراض المهنة المرافق لقانون التأمين الاجتماعى الصادر بالقانون رقم 79 لسنة 1975 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.